Paracetamol: A Boon to Medicine; A Dangerous Foe- Safe dosing of the Drug - Saxena, Dr. Ullas (International Journal Of Drug Research And Dental Science, 2025)
Paracetamol (Acetaminophen) is the most commonly used drug in the world, with a long record of use in acute and chronic pain. In recent years, the use of paracetamol has been questioned and controversial in some conditions like arthritis, back pain, spondylitis, Paget’s disease, bone and joint diseases, temporomandibular disorders, and in tumours and carcinomas. Over the same period, the adverse effects of paracetamol have increased, especially in patients with systemic disorders. The present review article summarises the history, indications, adverse effects, and also its uses in dentistry apart from medical use.